WOMEN'S PREFERENCE OF VAGINAL OR CAESAREAN DELIVERY: A CROSS SECTIONAL STUDY FROM A TERTIARY CARE HOSPITAL IN DISTRICT RAWALPINDI, PAKISTAN - Qamar, Mariam Khan; Shaikh, Babar Tasneem; Afzal, Aamir; Qamar, Armaghana Khan; Qamar, Yumna Khan (Journal of Ayub Medical College Abbottabad, 2021)
Background: In the wake of growing c- section rates around the developing world and likewise in Pakistan, there is paucity of knowledge about the preference of Pakistani women for the mode of delivery. Therefore, this study explored the reasons behind their preference. Methods: A cross-sectional study was conducted with a non-probability consecutive sampling technique including 232 pregnant women. Results: Majority (87.5%) would prefer a vaginal delivery because it is the natural way of giving birth and its recovery is faster. Moreover, women perceive that it would be easier to provide immediate care and breastfeeding to the newborn. Fear of surgery was the main deterrent for a c-section. Nonetheless, there were 12.5% women in favour of caesarean section, among whom a majority feared birth trauma to the newborn, labour pain, or complications of vaginal delivery such as possible faecal or urinary incontinence. Conclusion: Pakistani women at large prefer a normal vaginal delivery and therefore the rising trends of c- section cannot be attributed to the demand of the expecting women. Hence, there is a need for elucidating and explicating the real and perhaps the undisclosed reasons for the rising rates of caesarean section as a mode of delivery in Pakistan.